Efficacy of Aloe secundiflora crude plant extract against Candida albicans and Penicillium marneffei - Ndiba, Patrick Mutharia; Waihenya, Rebecca (African Journal of Science, Technology and Social Sciences, 2022)
Abstract Medicinal plants have been used in production of various drugs singly or in combination and even as principal raw material for the production of other conventional medicines. There are a number of Aloe species that grow wildly in Kenya. Ten mature leaves of Aloe secundiflora were collected and the crude plant extract was obtained and prepared according to Waihenya et al., 2003. It was then tested for antifungal activity against Candida albicans and Penicillium marneffei. In- vitro studies on the efficacy of crude extracts of A. secundiflora on C.albicans and P. marneffei were conducted. The results of the study revealed considerable zones of inhibition of Candida albicans growth caused by Aloe secundiflora crude plant extract on Sabouraoud agar. There was also growth inhibition of the Penicillium marneffei which is known to cause infections in immunosuppressed hosts and in non-AIDS patients with hematological malignancies and those receiving immunosuppressive therapy. Our results suggests that, the extract can be used to prevent the aflatoxins caused by Aspergillus species and the superficial mycosis that result from fungal infection and probably any other kind of mycoses. Further studies are required starting with experimental models to establish the in-vivo activity of the crude extract, the active ingredient, dosage and safety of A.secundiflora, before recommending it for clinical use. Keywords: Aloe secundiflora, Immunosuppressed hosts, Crude extract, Candida albicans, Penicillium marneffei